Autoimmune Hepatitis with Elevated Serum IgG4 Levels Have a High Prevalence of Cirrhosis at Diagnosis - Mei Xue; Yi Shen; Xiaoli Fan; Mengyi Shen; Li Yang (Canadian Journal of Gastroenterology and Hepatology)
Background. Some autoimmune hepatitis (AIH) patients have elevated serum IgG4 levels, and the clinical characteristics of such patients are currently incompletely characterized. Aim. To analyze the clinical features and possible pathogenesis of AIH with elevated serum IgG4 levels. Methods. According to their serum IgG4 value, patients were divided into elevated IgG4 (IgG4 > 1.35 g/l) and normal IgG4 (IgG4 ≤ 1.35 g/l) groups. Results. Among the 152 patients included in this study, those in the elevated IgG4 group had the following characteristics: older onset age (56 ± 11.43 years vs. 49.49 ± 13.04 years, P=0.005), higher proportion of males (34.15% vs. 12.61%, P=0.002), higher prevalence of cirrhosis (56.10% vs. 36.04%, P=0.026), lower prevalence of extrahepatic autoimmune diseases (9.76% vs. 27.3%, P=0.023), and higher levels of IL-17 and IL-22 (P<0.05). Logistic regression analysis results showed that elevated serum IgG4 levels and male sex were risk factors for AIH cirrhosis (male: odds ratio (OR) = 4.293, 95% confidence interval (CI): 1.592–11.575, P=0.004; and elevated serum IgG4: OR = 2.566, 95% CI: 1.065–6.187, P=0.036). No significant differences were found for the remission rate within 6 months between the two groups (69.70% vs. 76.14%, P=0.470). Conclusion. The male proportion and cirrhosis prevalence were higher in AIH with elevated serum IgG4 levels at the time of diagnosis. Male sex and elevated serum IgG4 levels are independent risk factors for AIH cirrhosis, and TH17 cells are more likely involved in the pathogenesis of this type of AIH.